Health system resilience: a literature review of empirical research - Biddle, Louise; Wahedi, Katharina; Bozorgmehr, Kayvan (Health policy and planning, 2020)
The concept of health system resilience has gained popularity in the global health discourse, featuring in UN policies, academic articles and conferences. While substantial effort has gone into the conceptualization of health system resilience, there has been no review of how the concept has been operationalized in empirical studies. We conducted an empirical review in three databases using systematic methods. Findings were synthesized using descriptive quantitative analysis and by mapping aims, findings, underlying concepts and measurement approaches according to the resilience definition by Blanchet et al. We identified 71 empirical studies on health system resilience from 2008 to 2019, with an increase in literature in recent years (62% of studies published since 2017). Most studies addressed a specific crisis or challenge (82%), most notably infectious disease outbreaks (20%), natural disasters (15%) and climate change (11%). A large proportion of studies focused on service delivery (48%), while other health system building blocks were side-lined. The studies differed in terms of their disciplinary tradition and conceptual background, which was reflected in the variety of concepts and measurement approaches used. Despite extensive theoretical work on the domains which constitute health system resilience, we found that most of the empirical literature only addressed particular aspects related to absorptive and adaptive capacities, with legitimacy of institutions and transformative resilience seldom addressed. Qualitative and mixed methods research captured a broader range of resilience domains than quantitative research. The review shows that the way in which resilience is currently applied in the empirical literature does not match its theoretical foundations. In order to do justice to the complexities of the resilience concept, knowledge from both quantitative and qualitative research traditions should be integrated in a comprehensive assessment framework. Only then will the theoretical ‘resilience idea’ be able to prove its usefulness for the research community.